Way Out West with Pirate Pete and Pirate Joe - Cannon, A. E. (Ann Edwards); Smith, Elwood H. 1941- (New York : Viking, 2006)
Two silly pirates go on a search for their Wild West cousins and end up at a surprise birthday party.
006-009.
1-3.
Keywords: Pirates -- Fiction; Birthdays -- Fiction; Fiction; West (U.S.) -- Fiction